Effect on the human normal microflora of oral antibiotics for treatment of urinary tract infections - Charlotta Edlund (2000)
Oral administration of antibiotics for treatment of urinary tract infections (UTIs) can cause ecological disturbances in the normal intestinal microflora. Poorly absorbed drugs can reach the colon in active form, suppress susceptible microorganisms and disturb the ecological balance. Suppression of the normal microflora may lead to reduced colonization resistance with subsequent overgrowth of pre-existing, naturally resistant microorganisms, such as yeasts and Clostridium difficile. New colonization by resistant potential pathogens may also occur and may spread within the body or to other patients and cause severe infections. It is therefore important to learn more about the ecological effects of antibacterial agents on the human microflora. The impact on intestinal microorganisms of oral antibiotics used for the treatment of UTIs is reviewed here. Ampicillin, amoxycillin and co-amoxiclav suppress both the aerobic and anaerobic intestinal microflora with overgrowth of ampicillin-resistant Enterobacteriaceae. Pivmecillinam also affects the intestinal microflora, suppressing Escherichia coli, but does not have a major effect on the anaerobic microflora. Several orally administered cephalosporins, such as cefixime, cefpodoxime, cefprozil and ceftibuten, reduce the number of Enterobacteriaceae and increase the number of enterococci. Colonization with C. difficile has also been observed. Fluoroquinolones eliminate or strongly suppress intestinal Enterobacteriaceae, but affect enterococci and anaerobic bacteria only slightly. When antimicrobial agents are prescribed for the treatment of UTIs, not only the antimicrobial spectrum of the agent but also the potential ecological disturbances, including the risk of emergence of resistant strains, should be considered.